Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Komitmen Organisasi terhadap Produktivitas Kerja Karyawan PT Madubaru PG. PS. Madukismo - Prema Vidya Santi; Nany Noor Kurniyati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study focuses on the influence of work environment, work discipline, and organizational commitment on work productivity. A quantitative approach using a survey method was used in this study, with 77 employees of PT Madubaru PG. PS. Madukismo as the sample selected randomly using random sampling. A Likert scale questionnaire was used to collect data, which was then analyzed using multiple linear regression to examine the influence between variables, both partially and collectively. The findings indicate that the work environment does not have a significant influence on work productivity (significance 0.134). Meanwhile, work discipline (significance 0.038) and organizational commitment (significance 0.000) were found to have a positive and significant influence on work productivity. The three variables together were proven to have a significant influence on work productivity (F value of 20.614 and Adjusted R Square of 43.6%).